Electromagnetic Modeling of the Passive Stabilization Loop at EAST - 戢翔 宋云涛 武松涛 王志滨 沈光 刘旭峰 曹磊 周自波 彭学兵 王成昊 (Plasma science & technology, 2012)
A passive stabilization loop （PSL） has been designed and manufactured in order to enhance the control of vertical instability and accommodate the new stage for high-performance plasma at EAST. Eddy currents are induced by vertical displacement events （VDEs） and disrup- tion, which can produce a magnetic field to control the vertical instability of the plasma in a short timescale. A finite element model is created and meshed using ANSYS software. Based on the simulation of plasma VDEs and disruption, the distribution and decay curve of the eddy currents on the PSL are obtained. The largest eddy current is 200 kA and the stress is 68 MPa at the outer current bridge, which is the weakest point of the PSL because of the eddy currents and the magnetic fields. The analysis results provide the supporting data for the structural design.